The prevalence of sickling abnormality in Oman: A review of relevant publications - Al-Mashaikhi, Nawal; Al-Rawas, Abdulhakim; Wali , Yasser; Soliman, Ashraf; Khater, Doaa (Acta Biomedica Atenei Parmensis, 2022)
Sickle cell disease (SCD), caused by a mutation in the β-globin gene HBB, is widely distributed in malaria endemic regions.  The prevalence of sickle cell trait and disease reaches up to 4.8–6% and 0.2% respectively, which is the highest among the Arab Gulf states.  Omani population represents a variability of HbS genotype combinations with other Hb genotypes modify the clinical severity of the disease. The most prevalent sickling abnormality in Oman is Hb S/S (SCA) followed by Hb S/β-thalassemia. Omani children with SCD with high Hb F level had less severe disease. More than two-thirds of SCD cases were running a mild course of the disease due to the high prevalence of  a-thalassemia trait. The severity index has been correlated with the early age of presentation, the absence of  a-thalassemia trait and the lower level of HbF as well as to the existence of different β-globin gene haplotypes.  S/ β0 presented with the same clinical severity of S/S while those with S/ β+ had some splenic function into adulthood and were more prone to splenic sequestration. The unique existence of HbS-Oman (a severe variant of sickle hemoglobinopathy) markedly increased the severity of the disease. Compound heterozygotes HbS-Oman resulted in very severe clinical manifestations with transfusion-dependency and hypersplenism early in life. This paper summarizes and reviews βs gene haplotypes in patients with sickle cell anemia (SCA) in Oman. (www.actabiomedica.it)